SAT0036 IL-17+CD8+ T cells enriched in the synovial fluid of PSA/SPA patients exhibit a pro-inflammatory cytokine phenotype. (15th June 2017) - Steel, KJA; Chan, E; Kirkham, BW; Taams, LS
Abstract : Background: Seronegative spondylarthropathies (SpA) share common clinical and immunological characteristics, including a common association with MHC class I, suggesting a role for CD8+ T cells. In contrast, rheumatoid arthritis (RA) is associated with MHC class II. We previously showed that IL-17+CD8+ T cells are increased in the synovial fluid (SF) of patients with psoriatic arthritis (PsA) but not RA, compared to peripheral blood (PB). This study extends this analysis to other SpA types, and phenotypes the SF IL-17+CD8+ T cells to further elucidate their potential pathogenic role. Methods: Paired PB and SF were collected from patients with RA, PsA and other SpA types (ankylosing spondylitis (AS), reactive arthritis (ReA), enteropathic arthritis (EA) and peripheral SpA (p-SpA)) from Guy's Hospital Rheumatology clinic with informed consent. PB from healthy controls (HC) was collected at King's College London. PBMC and SFMC were isolated and stimulated ex vivo with PMA/ionomycin in the presence of golgistop before analysis of surface marker and cytokine expression by flow cytometry. Results: The percentage of IL-17A+CD8+ T (Tc17) cells was increased in the SF of PsA (median 0.9%, p=0.0012, n=13) as well as other SpA patients (0.34%, p=0.0009, n=14), but not RA patients (0.07%, p=0.3, n=7) compared to matched PB (median 0.10%, no significant differences between disease and control PB). The percentage of SF IL-17A+CD4+ T (Th17) cells was increased in patients with SpA (2.14%, p=0.004, n=14), RA (2.31%, p=0.016, n=7) and to a lesser extent PsA (0.97%, p=0.057, n=13), compared to PB (median 0.61%, no significant differences between disease and control PB). Phenotypically, most SF IL-17A+CD8+ T cells expressed CCR6 (median 88%, n=7) and CD161 (75%, n=8), known markers of IL-17+CD4+ T cells. A high percentage also expressed CD103 (69%, n=9), which was not observed in the synovial IL-17A+CD4+ T cells (2%, n=10). A high frequency of IL-17A+CD8+ T cells co-expressed a range of pro-inflammatory cytokines including IFN-γ (72%, n=12), GM-CSF (58%, n=7), TNF-α (48%, n=12) and to a lesser extent IL-21 (20%, n=6) and IL-22 (5%, n=6). IL-10 was usually co-expressed at very low levels (1%, n=7), although 2 samples showed co-expression of IL-10 (33%, n=2). CCR6, CD161, GM-CSF and IL-21 were not significantly co-expressed by either IL-17A negative CD8+ or IFNg+CD8+ (Tc1) T cells from the SF, indicating this may be a co-expression profile specific to IL-17 expressing T cells. Conclusions: These findings confirm the presence of an IL-17A+CD8+ T cell subset in the SF of PsA patients and extend this to other SpA types. The expression of the integrin CD103 by these cells indicates they may represent a tissue resident memory (Trm) population in the synovial joint. In addition to IL-17A, the co-expression of several pro-inflammatory cytokines combined with low expression of IL-10, suggests a pro-inflammatory role for these cells. Acknowledgements: This work was funded in part by the King's Health Partners R&D Challenge Fund (R140808) and in part by research support from Novartis. Disclosure of Interest: K. Steel: None declared, E. Chan: None declared, B. Kirkham Grant/research support from: Novartis, UCB, Abbvie, Bristol Myer Sqibb, Celgene, Janssen, MSD, Pfizer, Roche, L. Taams Grant/research support from: Novartis and UCB